85 ESTABLISHING AN EMERGENCY PERIOPERATIVE FOR OLDER PERSONS SERVICE (POPS) IN A TERTIARY HOSPITAL SETTING: EARLY DATA. (18th November 2021) - Plant, R; Stanley, E; Dukelow, T; Kayyal, Y; Aherne, E
Abstract: Background: Evidence supports the role of geriatricians in perioperative settings. The success of orthogeriatrics has encouraged geriatric input into other surgical services. The British Geriatrics Society recommends early geriatric assessment for patients undergoing laparotomy as a means to improve older adult outcomes. We present the initial data of our Perioperative Older Person Service (POPS) that aims to standardise a clinical pathway for older adults admitted under an emergency surgical service using Comprehensive Geriatric Assessment (CGA). Methods: We obtained an additional a whole-time equivalent geriatric registrar to facilitate establishing the POPS. Inclusion criteria for assessment included those over 75 either admitted under an emergency surgical consultant, or awaiting a surgical assessment in the emergency department. A geriatrician performed a CGA for these patients. We collected data including; demographics, diagnosis; premorbid frailty status (Clinical Frailty Scale (CFS) score 2 weeks prior to admission); polypharmacy; 4AT score; admission and discharge destination; procedure performed; 30-day readmission rate; ICU admission; and 90-day mortality. Extra information was gathered using free-text to identify additional geriatric interventions. Results: At time of submission the service has assessed 15 patients over 21 days. 46% (7/15) were female, 54% (8/15) were male. 53% (8/15) of patients underwent CGA on the day of admission. 100% patients were assessed within 72 hours of their admission. 46% (7/15) had a CFS ≥4. 26% (4/15) were identified as delirious as per 4AT. 18.7% (3/16) had a procedure performed during their admission. We identified polypharmacy in 73% (11/15).46% (7/15) were discharged with reduced medication burden. CGA prompted new advanced care planning decisions in 40% (6/15) of patients. Conclusion: Although the service is in its infancy, the above data is encouraging. Through early identification of frailty and timely CGA, we anticipate this service will ensure the delivery of geriatrically-attuned care to frail older people and improve outcomes.